IMPACT OF SOCIAL DISTANCING IN CURBING COVID-19 PANDEMIC: A SYSTEMATIC REVIEW - M. Ammar Luthfi Kurniawan; Litania Leona Hidayat; Jihan Natra Shafira; Iche Andriyani Liberty (JURNAL KEDOKTERAN DAN KESEHATAN, 2021)
Social distancing includes strategies to ban public gatherings and advise individuals to stay at their home or maintain distance to one another by at least 1-2 meters. This study aims to intend to assess all the available evidence of social distancing in decreasing COVID-19 transmission in the general population. We conducted an electronic search of published literature using MEDLINE/Pubmed, Science direct, PMC, Wiley, and Google Scholar and we use Joanna Briggs Institute (JBI) critical appraisal checklist to assess methodological qualities. A total of 7 articles were decided to be included in this study. Social distancing has curb down the number and saved approximately 10 thousand Brazilian lives. A study by VoPham et al on the association of social distancing and COVID-19 incidence found higher social distancing was associated with a 29% reduction of COVID-19 incidence (adjusted IRR 0.71;95% CI (0,57-0,87) and 35% reduction of COVID-19 mortality (adjusted IRR 0,65; 95% CI 0,55-0,76). Social distancing is one of the major policies implemented for long-term behavioral adjustment in managing the COVID-19 pandemic. Passive social distancing is not enough to drag down the number, there needs to be large scale testing, isolation, and contact tracing. However, we believe we have illuminated the impact of social distancing on the COVID-19 pandemic and add to the available literature the basis of social distancing in reducing transmission of COVID-19.